HEart and BRain interfaces in Acute ischemic Stroke (HEBRAS) – rationale and design of a prospective oberservational cohort study. Issue 1 (December 2015) - Haeusler, Karl; Grittner, Ulrike; Fiebach, Jochen; Endres, Matthias; Krause, Thomas; Nolte, Christian
Abstract Background An effective diagnostic work-up in hospitalized patients with acute ischemic stroke is vital to optimize secondary stroke prevention. TheHEart and BRain interfaces in Acute ischemic Stroke (HEBRAS) study aims to assess whether an enhanced MRI set-up and a prolonged Holter-ECG monitoring yields a higher rate of pathologic findings as compared to diagnostic procedures recommended by guidelines (including stroke unit monitoring for at least 24 h, echocardiography and ultrasound of brain-supplying arteries). Methods/Design Prospective observational single-center study in 475 patients with acute ischemic stroke and without known atrial fibrillation. Patients will receive routine diagnostic care in hospital as wells as brain MRI, cardiac MRI, MR angiography of the brain-supplying arteries and Holter-monitoring for up to 10 days. Study patients will be followed up for cardiovascular outcomes at 3 and 12 months after enrolment. Discussion By comparing the results of routine diagnostic care to the study-specific MRI/ECG approach, the primary outcome of HEBRAS is the proportion of stroke patients with pathologic diagnostic findings. Predefined secondary outcomes are the association of stroke localization, autonomic dysbalance and cardiac dysfunction as well as the effect of impaired heart-rate-variability on long-term clinical outcome. The investigator-initiated HEBRAS study will assess whether an enhanced MRI approach and a prolonged ECG monitoring yield a higher rate of pathological findings than current standard diagnostic care to determine stroke etiology. These findings might influence current diagnostic recommendations after acute ischemic stroke. Moreover, HEBRAS will determine the extent and clinical impact of stroke-induced cardiac damage. Trial registration Clinicaltrials.govNCT02142413 .